Effects of Alteplase for Acute Stroke on the Distribution of Functional Outcomes: A Pooled Analysis of 9 Trials. Issue 9 (September 2016) - Lees, Kennedy R.; Emberson, Jonathan; Blackwell, Lisa; Bluhmki, Erich; Davis, Stephen M.; Donnan, Geoffrey A.; Grotta, James C.; Kaste, Markku; von Kummer, Rüdiger; Lansberg, Maarten G.; Lindley, Richard I.; Lyden, Patrick; et al.
Abstract : Background—: Thrombolytic therapy with intravenous alteplase within 4.5 hours of ischemic stroke onset increases the overall likelihood of an excellent outcome (no, or nondisabling, symptoms). Any improvement in functional outcome distribution has value, and herein we provide an assessment of the effect of alteplase on the distribution of the functional level by treatment delay, age, and stroke severity. Methods—: Prespecified pooled analysis of 6756 patients from 9 randomized trials comparing alteplase versus placebo/open control. Ordinal logistic regression models assessed treatment differences after adjustment for treatment delay, age, stroke severity, and relevant interaction term(s). Results—: Treatment with alteplase was beneficial for a delay in treatment extending to 4.5 hours after stroke onset, with a greater benefit with earlier treatment. Neither age nor stroke severity significantly influenced the slope of the relationship between benefit and time to treatment initiation. For the observed case mix of patients treated within 4.5 hours of stroke onset (mean 3 hours and 20 minutes), the net absolute benefit from alteplase (ie, the difference between those who would do better if given alteplase and those who would do worse) was 55 patients per 1000 treated (95% confidence interval, 13–91; P =0.004). Conclusions—: Treatment with intravenous alteplase initiated within 4.5 hours of stroke onset increases the chance of achieving an improved level of function for all patients across the age spectrum, including the over 80s and across all severities of stroke studied (top versus bottom fifth means: 22 versus 4); the earlier that treatment is initiated, the greater the benefit. Abstract : Supplemental Digital Content is available in the text.